"Electrons-siphoning" of sulfate reducing bacteria biofilm induced sharp depletion of Al-Zn-In-Mg-Si sacrificial anode in the galvanic corrosion coupled with carbon steel. (15th May 2023) - Zhang, Tiansui; Wang, Zhengyun; Qiu, Yubing; Iftikhar, Tayyaba; Liu, Hongfang
Abstract: The microbiologically influenced corrosion (MIC) of Al-Zn-In-Mg-Si sacrificial anode coupled with X80 carbon steel induced by sulfate reducing bacteria (SRB) was investigated. Results revealed that SRB strongly promoted the galvanic current density between the aluminum anode and carbon steel by facilitating the cathodic process of the galvanic corrosion on carbon steel. In the medium with SRB, 73.7% of the corrosion loss of aluminum anode coupled to carbon steel was caused by the enhanced galvanic corrosion. SRB biofilm on the carbon steel continuously obtained electrons from the aluminum anode, which was like an "electrons-siphoning" process in the galvanic corrosion. Highlights: The galvanic current density between aluminum anode and carbon steel is greatly promoted in SRB inoculated medium. SRB can result in a larger potential difference between carbon steel and aluminum anode. SRB biofilm on carbon steel promotes the cathodic process and thereby accelerates the aluminum anode depletion. The enhanced cathodic process is related to the electrons uptake by SRB and certain substances in the biofilm.